The Effect of Breast Self-Examination Health Education on Knowledge and Motivation to Perform Breast Self-Examination in Adolescent Females at The SMAN 2 Way Tenong - Desri Ayu, Juwita; Anggraini, Diana; Anggista Putri, Nopi; Dari, Wulan (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: In Indonesia, the number of breast cancer patients is estimated to increase by around 65,000 new cases each year, with 70% of new cancer patients visiting the doctor at the final stage. One of the causes of the high number of breast cancer cases is a lack of knowledge, motivation, and desire to undergo early detection examinations. SADARI is a self-breast examination to detect any abnormalities in the breasts. This study aims to determine the effect of health education about SADARI on knowledge and motivation to perform SADARI among female adolescents at SMAN 2 Way Tenong. Method: This study is a pre-experimental study using a one-group pretest-posttest design. The population consists of 31 female adolescents at SMAN 2 Way Tenong. The sample used is 31 female adolescents at SMAN 2 Way Tenong. The sampling technique used is total sampling. The instrument used was a questionnaire, and the study was conducted on November 13, 2024, with data analyzed using the Wilcoxon Signed Rank Test. Result: The average knowledge about SADARI before the intervention was 48.3% (low knowledge), while the average after the intervention was 91.1% (good knowledge). The average motivation to perform SADARI before was 32.9% (low motivation), while the average after was 90.5% (high motivation). There was an effect of SADARI health education on knowledge with a p-value of 0.000 > 0.05. Conclusion: There is an effect of SADARI health education on motivation to perform SADARI, with a p-value of 0.000 > 0.05. It is hoped that this research can provide information about SADARI to adolescent girls, serve as a reference for education and counseling for high schools and health workers, become a source of publication and literature, and be used as a reference for Aisyah Pringsewu University.